PANCASILA SEBAGAI LANDASAN ILMU PENGETAHUAN DALAM MEMBANGUN PERADABAN BANGSA - Hulu, Ira Asnita (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
Pancasila is the basic ideology of the Indonesian state which is not only a guideline in national and state life, but also acts as a basis for science. This article explores how Pancasila can become a foundation for the development of science based on national values and social justice. An analytical approach is used to examine the relevance of Pancasila values to the development of science, as well as connecting theory with practice in various fields. The results of the discussion show that Pancasila is able to provide an ethical and moral framework for the use of science for the benefit of the wider community.